The Scottish Presbyterian Defence of British Protestantism: The Scottish Reformation Society and the “Papal Aggression”, 1850–52 - Mallon, Ryan (Journal of religious history, 2022)
This article is a study of the Edinburgh-based anti-Catholic organisation, the Scottish Reformation Society, in the immediate aftermath of the 1850 restoration of the Roman Catholic hierarchy in England and Wales, commonly known at the time as the papal aggression. The papal aggression sent shockwaves throughout England and was viewed by Protestants as an illegal attempt to overthrow Britain's civil and religious liberties by Pope Pius IX. Despite in practice only affecting England, the restoration also had a dramatic impact in Scotland, resulting in thousands of parliamentary petitions and sporadic bouts of communal violence. The Scottish Reformation Society, led by the controversial Free Church of Scotland minister James Begg, was at the forefront of this Scottish Protestant response. The society was dominated by Scotland's Presbyterian dissenters, particularly members of the establishmentarian Free Church. The Free Church had formed out of the 1843 Disruption in the Established Church of Scotland, a momentous politico-ecclesiastical event which highlighted divisions between the British state and its Scottish church, the national kirk and dissent, and pro-establishment and voluntary ecclesiologies. By focusing on the influence of a major Scottish anti-Catholic society during a turbulent period for British Protestantism, this article examines the gulf between the rhetoric of national Protestant unity and the reality of national, ideological, and denominational divisions within mid-nineteenth century Protestantism in the United Kingdom. It builds on existing research to highlight the various ways in which the anti-Catholic movement was fractured on denominational lines and reflected the wider tensions of Scottish ecclesiastical politics in the years after the Disruption.